Career opportunities in library and information science - Taylor, T. Allan; Parish, James Robert (New York : Ferguson, 2009)
Whether you're a student or a professionals ready for a career change, you'll find in this invaluable book everything you need to know to start an exciting career or alter the direction of your current career in library and/or information science. Features include a quick-reference Career Profile for each job summarizing its notable features, a Career Ladder illustrating frequent routes to and from the position described, and a comprehensive text pointing out special skills, education, training, and various associations relevant to each post. Appendixes list educational institutions, periodicals and directories, professional associations, and useful industry Web sites.
Description based on print version record.
Includes bibliographical references (p. 352-354) and index.
Keywords: Library science -- Vocational guidance -- United States -- Juvenile literature; Information science -- Vocational guidance -- United States -- Juvenile literature; Librarians -- Employment -- United States -- Juvenile literature; Librarians -- Job descriptions -- United States -- Juvenile literature; Electronic books; Electronic books